Subject: Letter to the editor regarding the article “A systematic review on the effects of direct oral anticoagulants on cancer growth and metastasis in animal models” - Al-Azzawi, Huda Moutaz Asmael; Celentano, Antonio (Thrombosis research, 2024)
•Reviewing the article entitled “A systematic review on the effects of direct oral anticoagulants on cancer growth and metastasis in animal models”•One of the included studies in this systematic review does not meet the predefined inclusion criteria of the study and it does not meet the strict definition of an animal cancer model.•We have highlighted the study and illustrated its purpose, as well as how it fails to measure the specific parameters that the authors were seeking in their research, as it is entirely focused on a different subject matter•Ensuring the accuracy and relevance of the studies included in systematic reviews is essential for upholding the integrity and validity of the findings presented.